Early impact of rotavirus vaccination in a large paediatric hospital in the UK. Issue 2 (June 2016) - Hungerford, D.; Read, J.M.; Cooke, R.P.D.; Vivancos, R.; Iturriza-Gómara, M.; Allen, D.J.; French, N.; Cunliffe, N.
Summary: The impact of routine rotavirus vaccination on community-acquired (CA) and healthcare-associated (HA) rotavirus gastroenteritis (RVGE) at a large paediatric hospital, UK, was investigated over a 13-year period. A total of 1644 hospitalized children aged 0–15 years tested positive for rotavirus between July 2002 and June 2015. Interrupted time-series analysis demonstrated that, post vaccine introduction (July 2013 to June 2015), CA- and HA-RVGE hospitalizations were 83% [95% confidence interval (CI): 72–90%) and 83% (95% CI: 66–92%] lower than expected, respectively. Rotavirus vaccination has rapidly reduced the hospital rotavirus disease burden among both CA- and HA-RVGE cases.